The spoken word. Poets historic recordings of poets born in the 19th century - British Library. National Sound Archive (Yokshire : The British Library Publication, 2003)
Features the earliest recordings of English-language poets whose voices survive. The poets, all of whom were born before 1900, are presented in chronological order of birth, starting with Tennyson and Browning and ending with Robert Graves.
Contents on sound disk : Charge of the light brigade (2:26) - How they brought the good (0:52) - Vitai lampada (1:18) - Drake's drum (1:38) -Introduction (1:57) -The Lake Isle of Innisfree (1:25) -France [estract] (0:45) -For the fallen (2:47) -Tarantella (1:31) - Nod (1:05) -Song of shadow (0:52) - A valentine to sherwood Anderson (3:45) -Stopping by woods on a snowy evening (0:48) - Sea fever (1:09) -The highwayman (6:07)-The alien (1:26) - Cotswold love (0:50) - Mrs Willow (1:47) -Spring and all [ by the road to the montagious hospital,1945] - Queen-Anne's -lace (0:52) - The seafarer (7:08) - Attack (1:00) - Died of wounds (0:52)-To the stone cutters (0:50) -Jodelling song [from facade] - A man from a far countree [from facade] (1:18) - The love song of J. Alfred Prufrock(7:53) - The watergaw (1:56) - The Eemis Stane (1:23) - My father moved through dooms of love(5:36) - In parenthesis[extract from part 7] -1805 (2:10)
Keywords: Poets, English -- 19th century; Poets, English -- 20th century; Poets, American -- 20th century